2021
DOI: 10.53333/ijicc2013/15941
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Malnutrition and Tuberculosis (TB) At The Age Group More Than 18 Years Old In Indonesia (Analysis Of The Basic Health Research 2018)

Abstract: The study aimed to determine the relationship between nutritional status based on Body Mass Index (BMI) and Tuberculosis (TB) in the age group >18 years. This study further analyzes the 2018 Basic Health Research (Riskesdas 2018), a cross-sectional study conducted in all city districts in 34 provinces of Indonesia. Unit samples of this study are population-based in the age group >18 years. The determination of having had TB is if the respondent answered yes to the question: "Has a doctor ever been diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This is related to the immune response of a child. Respiratory disease is often associated with malnutrition and stunting in children [42]. Children who suffer from infectious diseases with a longer duration of time are more likely to experience stunting so that they are 2.3 times more likely to experience stunting compared to children who do not have a history [43].…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the immune response of a child. Respiratory disease is often associated with malnutrition and stunting in children [42]. Children who suffer from infectious diseases with a longer duration of time are more likely to experience stunting so that they are 2.3 times more likely to experience stunting compared to children who do not have a history [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been noted that there was a significantly higher prevalence of anemia and decreased retinol and zinc titers in the plasma collected from TB patients in Jakarta (Karyadi et al, 2000). Additionally, a 16.7fold greater risk of acquiring TB was found in TB patients whose body mass index (BMI) was below the normal range (Tobing et al, 2021). Furthermore, a case study in Medan, North Sumatra revealed that malnutrition accounts for 31.25% and 36.3% of TB patients suffering from HIV co-infection and those experiencing treatment failure, respectively (Ritonga, 2020).…”
Section: Health Conditionsmentioning
confidence: 99%
“…This relationship can be attributed to the heightened level of activity associated with productive age, which increases the susceptibility of individuals to exposure from TB patients. According to Tobing et al (2021), a significant proportion of tuberculosis (TB) patients in Indonesia belong to the 15-54 year age group, which constitutes 56% of the total cases. Additionally, a majority of these patients are diagnosed with co-morbidities, particularly HIV/AIDS.…”
Section: Multivariate Analysismentioning
confidence: 99%